A) (3√50 + 2√8 - √32) : √2
b) (6√24 - √√54 + 96) : √3
c) (8 ∛16 + 2∛54 - 3∛128) : ∛2
d) (4∛625 - 3∛40 + ∛320) : ∛5
e) (5√28 - 3√7 + √63) : √7
f) (∛24 + ∛81 - ∛375) : ∛3

Prosiłabym o ładne rozpisanie przykładów i szybkie, poprawne wykonanie zadania.

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T14:20:07+01:00
A) (3√50 + 2√8 - √32) : √2=3√50/√2+2√8/√2 - √32/√2=
=3√(50/2)+2√(8/2)-√(32/2)=3√25+2√4-√16=3*5+2*2-4=15
b) (6√24 - √54 + √96) : √3=6√24 /√3- √54 /√3+ √96/√3=
=6√(24/3)-√(54/3)+√(96/3)=6√8-√18+√32=6√(4*2)-√(9*2)+√(16*2)=
=6*2√2-3√2+4√2=12√2-3√2+4√2=13√2
c) (8 ∛16 + 2∛54 - 3∛128) : ∛2=8 ∛16/∛2+ 2∛54/∛2 - 3∛128/∛2=
=8∛(16/2)+2∛(54/2)-3∛(128/2)=8∛8+2∛27-3∛64=8*2+2*3-3*4=
=16+6-12=10
d) (4∛625 - 3∛40 + ∛320) : ∛5=4∛625/∛5 - 3∛40∛5 + ∛320∛5=
=4∛(625/5)-3∛(40/5)+∛(320/5)=4∛125-3∛8+∛64=4*5-3*2+4=20-6+4=18
e) (5√28 - 3√7 + √63) : √7=5√28/√7 - 3√7/√7 + √63/√7=
5√(28/7)-3+√(63/7)=5√4-3+√9=5*2-3+3=10
f) (∛24 + ∛81 - ∛375) : ∛3=∛24/∛3 + ∛81/∛3 - ∛375/∛3=
=∛(24/3)+∛(81/3)-∛(375/3)=∛8+∛27-∛125=2+3-5=0